Política de atenção ao tabagista no município de Vitória-ES : olhares e caminhos para a sua (re)configuração - França, Marilene Gonçalves (2013)
By promoting smoking cessation, The Brazilian National Tobacco Control Policy allowed the smoker s health care policy to be inserted into the Brazilian Unified Health System network. In this setting, it is necessary to understand how this policy has been carried out at municipal level in order to figure out the relationships established and the arrangements made in this process. This study aims at analyzing the implementation of the smoker s health care policy seen through the eyes of the Municipal Tobacco Coordination, the relevant professionals, and the users of the Tobacco Control Program in the City of Vitória, ES, Brazil. This is a case study with qualitative approach through critical discourse analysis, seeking a dialogue with the theoretical area of public health. The study was carried out in three stages: the first one was made up of bibliographical review on tobacco smoking, tobacco control policies, the Brazilian National Tobacco Control Program and its insertion into the Brazilian health care policy. The second stage comprised an analysis of official documents of federal and municipal normative instruments, and analysis of primary 2011 data on the Brazilian Tobacco Smoking Control Program. The third stage included interviews between March and August 2012 with the actors in this program: the municipal coordination, the professionals at health care units, and the program users. The subjects involved considered the smoker s health care policy well planned, functional and effective. It meets the health care needs of individuals with tobacco-related problems and has positive results in the users lives. However, some challenges were listed in this process, such as effectively making the policy a priority in the city; instituting, besides monitoring, a political assessment; creating a permanent space for dialogue between the actors who implement this policy; rethinking the strategies and methodologies proposed. This study allowed us to understand the process of implementing public policies as an integration and interaction process between several actors who give life to this policy, contributing to (re)configuring smoker s health care.